2018
DOI: 10.3389/fpsyg.2018.01384
|View full text |Cite
|
Sign up to set email alerts
|

Eye Movement Desensitization and Reprocessing Versus Treatment as Usual in the Treatment of Depression: A Randomized-Controlled Trial

Abstract: Eye movement desensitization and reprocessing (EMDR) is a well-established treatment for post-traumatic stress disorder. Recent research suggested that it may be effective in treating depressive disorders as well. The present study is part of a multicenter randomized-controlled trial, the EDEN study, in which a homogenous group of 30 patients was treated to test whether EMDR plus treatment as usual (TAU) would achieve superior results compared to TAU only in a psychosomatic-psychotherapeutic inpatient treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 33 publications
(42 reference statements)
3
31
0
4
Order By: Relevance
“…This model is supported by studies that identify measures of EMS as mediators of the relationship between aversive early‐life events and subsequent depressive life symptoms (Cukor & McGinn, 2006; Roelofs, Lee, Ruijten, & Lobbestael, 2011). Further, similar to schema therapy, the AIP model that has been proposed to underlie EMDR suggests that current depressive symptoms can be changed by targeting memories that are aetiologically related to the psychopathology (Hase et al , 2018). In CBT and schema‐based approaches, clients are often educated about the importance of past adversities in precipitating current thoughts and behaviours (Beck & Beck, 1995; Young et al , 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This model is supported by studies that identify measures of EMS as mediators of the relationship between aversive early‐life events and subsequent depressive life symptoms (Cukor & McGinn, 2006; Roelofs, Lee, Ruijten, & Lobbestael, 2011). Further, similar to schema therapy, the AIP model that has been proposed to underlie EMDR suggests that current depressive symptoms can be changed by targeting memories that are aetiologically related to the psychopathology (Hase et al , 2018). In CBT and schema‐based approaches, clients are often educated about the importance of past adversities in precipitating current thoughts and behaviours (Beck & Beck, 1995; Young et al , 2003).…”
Section: Discussionmentioning
confidence: 99%
“…While there are three randomized controlled trials (RCTs) comparing TFTs as an adjunct therapy for depression (Hase et al , 2018; Minelli et al , 2019; Ostacoli et al , 2018), and two as a stand‐alone therapy (Gauhar & Wajid, 2016; Moritz et al , 2018), no study to date has compared a TFT with an alternative treatment and treatment as usual (TAU). This is important because the inclusion of an active control could help determine if the TFT per se was responsible for any additional improvement beyond TAU, or whether any targeted depression treatment might achieve the same effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past 5 years, several studies have been conducted demonstrating preliminary evidence for the efficacy of EMDR therapy in the treatment of MDD in adults. Promising results were obtained from studies investigating EMDR therapy as an adjacent therapy to CBT (Hofmann et al, 2014), to pharmacological treatment (Minelli et al, 2019;Ostacoli et al, 2018) and to inpatient treatment (Hase et al, 2015(Hase et al, , 2018. Three studies, investigating the efficacy of EMDR as a stand-alone treatment, demonstrated significant reductions of depressive symptoms (Gauhar, 2016), even for patients with long-term depression (Wood, Ricketts, & Parry, 2018) and treatment-resistant depression (Minelli et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…B. Angst-, depressive und phobische Störungen und Suchterkrankungen ausgeweitet. Es zeichnet sich ab, dass eine Wirksamkeit auch für diese Indikationen nachgewiesen werden kann [11]. Damit wird EMDR zu einer Behandlungsmethode, die potenziell bei allen psychischen Störungsbildern eingesetzt werden kann, bei denen stressauslösende Erinnerungen eine ursächliche Rolle spielen.…”
Section: Fa Zitunclassified